Projeto, desenvolvimento, otimização e scale-up de um leito fluidizado para classificação de fosfato bicálcico microgranulado - Ribas, Rogério Marques (2006)
Brazil holds second place in world production of dicalcium phosphate, which represents the main source of phosphorus for complementing the mineral salt that makes up the daily feed for cattle, hogs and fowls. Considering the fact that the increase in consumption of phosphates due to the increased annual consumption of meat by the world population, development of the technology necessary to guarantee quality and productivity has become imperative in order to supply this competitive market. The requirement for BUNGE Fertilizantes S.A. to accompany the world trend, reflected by client suggestions for sales of bulk quantities, originated the search for a new technology to produce microgranulated dicalcium phosphate. Due to characteristics adverse to forming the microgranulated dicalcium phosphate grain (particle size, monocalcium phosphate and residual acidity), it has become necessary to apply a final product classification process to guarantee compliance with the physical specifications of the material at the moment of expediting to clients. The purpose of this dissertation is to perform a study of the classification system used for fluidization, seeking scale-up information for construction of an industrial unit to be installed at the Cajati Facilities of BUNGE Fertilizantes. Fluidization is utilized commercially in a wide range of processes such as: catalytic operations, cooling, drying, recovery, etc, it utilizes the elutriation effect in wich the relatively small components are entrained by the gas flow for physical classification of materials. Within this concept an effort was made to quantify the effects of operational and dimensional variables of the fluidized bed system: porosity of the distribuition screen, residence time and freeboard angle. In accordance with the main experimental results, a statistical analyses was made by multiple regression, thus obtaining parameters related to the isolated variables and the interactions among them. It was observed that the operational and dimensional conditions that promote the best Separation and Recovery efficiencies for the system were those for which the screen porosity was 11 %, the residence time was 5,34 minutes and the freeboard angle was 33,62o. On the basis of the optimum data obtained from the fluidization pilot system, an industrial system was designed for the Cajati Facilities, having classification capacity of microgranulated dicalcium phosphate of 100 Tons/h. The resultant Separation end Recovery efficiencies of the industrial system demonstrate an excellent application of technology for FBC (dicalcium phosphate) classification and the model obtained from the pilot project precisely predicts the efficiencies for industrial systems. Thus, the mathematic model obtained from the pilot plant can be used as a reference for design and scale-up of microgranulated dicalcium phosphate industrial classification units, having characteristics similar to those studied in this dissertation.